EFFECTIVENESS OF TOPICAL BACTERIAL LYSATES IN TREATMENT OF ACUTE RESPIRATORY INFECTIONS IN YOUNGER SCHOOLCHILDREN IN ORGANIZED GROUPS - S.Yu. Artemova; T.E. Taranushenko; Z.N. Goncharuk ("Paediatrician" Publishers LLC, 2008)
An experience of treatment of younger schoolchildren with acute respiratory infections (ARI) with bacterial lysates mixture (IRS 19) is presented. This medication favors to rapid regress of clinical signs of disease and to acceleration of a recovery. Cellratio in mucus, produced by mucous tunic of fauces and nasal cavity differs under the influence of treatment: the number of neutrophils and macrophages decreases, and the number of epiteliocytes increases. The 4 months prospective trial showed that use of mixture of bacterial lysates in younger school children greatly decreases the risk of incidence of new cases of ARI.Key words: younger schoolchildren, acute respiratory infections, bacterial lysates mixture.